2016
DOI: 10.1007/s10452-016-9588-x
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic hyphomycetes, benthic macroinvertebrates and leaf litter decomposition in streams naturally differing in riparian vegetation

Abstract: Small forest streams and their riparian vegetation are closely linked ecosystems. Stream consumers obtain most of their energy from leaf litter provided by the terrestrial vegetation. Thus, understanding the relationship between riparian vegetation, aquatic communities and litter decomposition may help explaining the variability in aquatic communities and processes among non-impacted streams, and anticipate their responses to anthropogenic-induced changes in the riparian vegetation. We surveyed 10 small non-im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 79 publications
4
51
0
3
Order By: Relevance
“…Our results showed that ALAN increased leaf litter decomposition and decreased lignin content, indicating that ALAN exposure can stimulate litter decomposition directly by increasing the microbial accessibility to lignin, as well as by increasing the labile carbon supply to microbes since lignin, as an effective light-absorbing compound, can preferentially degrade over a wide range of wavelengths [37,39]. In addition, variation in the fungal community structure is also an important factor affecting leaf litter decomposition [19,40,41]. Our results showed that the relative abundance of the most abundant species (named unclassified_d__Eukaryota) was significantly lower in ALAN treatments than that in the control (N treatment) but the next most abundant species, including ones named unclassified_o__Monhysterida and unclassified_o__Pleosporales, were significantly higher in ALAN treatments (Figure 2a).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that ALAN increased leaf litter decomposition and decreased lignin content, indicating that ALAN exposure can stimulate litter decomposition directly by increasing the microbial accessibility to lignin, as well as by increasing the labile carbon supply to microbes since lignin, as an effective light-absorbing compound, can preferentially degrade over a wide range of wavelengths [37,39]. In addition, variation in the fungal community structure is also an important factor affecting leaf litter decomposition [19,40,41]. Our results showed that the relative abundance of the most abundant species (named unclassified_d__Eukaryota) was significantly lower in ALAN treatments than that in the control (N treatment) but the next most abundant species, including ones named unclassified_o__Monhysterida and unclassified_o__Pleosporales, were significantly higher in ALAN treatments (Figure 2a).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, other studies ( Fenchel 1993 , Finlay and Clarke 1999 , Finlay 2002 , Finlay and Fenchel 2004 ) suggested the high capacity of dispersal of microorganisms with few geographical barriers when compared to macroorganisms, such as freshwater macroinvertebrates ( Hughes et al 1998 , Hughes and Malmqvist 2005 , Raposeiro et al 2012 ). While at the global scale, most of the aquatic hyphomycetes species have a cosmopolitan distribution (although some level of endemism was observed in some studies; see Duarte et al 2016a , Seena et al 2019 ), at a local scale, their assemblages are strongly influenced by environmental factors that dominate over the spatial processes ( Barlocher and Graça 2002 , Gulis and Suberkropp 2003 , Rajashekhar and Kaveriappa 2003 , Heino et al 2004 , Ferreira et al 2006a , Cornut et al 2012 , Ferreira et al 2016a , Duarte et al 2017 ), which can explain the differences in the distribution of aquatic hyphomycetes species observed in Madeira streams. This is in line with the hypothesis of Baas-Becking (1934) , which claims that “everything is everywhere”, but microbial assemblages are controlled by environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…Habitat : Submerged leaf litter [e.g. Acacia melanoxylon , Acer rubrum , Clethra arborea , Cryptomeria japonica , Eucalyptus globulus Labill., Ilex perado , Pittosporum undulatum , Rhododendron maximum ( Gulis and Suberkropp 2003 , Ferreira et al 2006b , Gonçalves et al 2007 , Ferreira et al 2016a , Ferreira et al 2017 )].…”
Section: Checklistsmentioning
confidence: 99%
“…Microbial decomposition is strongly influenced by water chemistry, particularly phosphorus, as well as temperature. Higher phosphorus can promote faster fungal growth on leaf material, thereby, creating higher quality, more preferential conditions for shredder‐mediated decomposition (Ferreira et al, ; Ferreira, Castela, et al, ; Suberkropp & Chauvet, ). Of the incubation streams used in this study, both reference sites had higher phosphorus levels than either fire‐disturbed site; however, we did not measure parameters related to microbial community composition or activity and can therefore only speculate that this water quality difference may partially explain the differences in litter decomposition rates between streams.…”
Section: Discussionmentioning
confidence: 99%